DETERMINATION OF VISUAL ACUITY AND VISUAL AXIS OF BROWNMARBLED GROUPER, Epinephelus fuscoguttatus TO DEVELOP A DEMAND FEEDING SYSTEM - Nai, Han Tan; Firdaus2, Rian Freddie; Yukinori, Mukai (Malaysian Journal of Science, 2013)
The visual acuity and visual axis of juvenile brown-marbled grouper, Epinephelus fuscoguttatus were determined to get the understanding of their vision in order to develop a demand feeding system. Three juveniles were anaesthetised with MS222 and fixed in Bouin’s solution. The left retina of each juvenile was cut into nine regions – the dorso-nasal (DN), dorsal (D), dorso-temporal (DT), nasal (N), bottom (B), temporal (T), ventro-nasal (VN), ventral (V), and ventro-temporal (VT). The specimens were embedded in paraffin, cut into 6 µm thick tangential sections, and stained with haematoxylin-eosin. The density of cone cells (0.01 mm2 ) in each region was counted in the stained sections. Visual acuity was calculated using cone cell densities and lens diameter. The highest cone cell densities of each of the juveniles were 359 (bottom, B), 394 (temporal, T), and 380 cells/0.01 mm2 (temporal, T), respectively. The estimated visual acuities were 0.068-0.081 in those regions, respectively. These results showed that the visual axis of brown-marbled grouper juveniles was forward. Therefore, the position of the target switch of demand feeding system was set at 2 cm below the water surface. ABSTRAK Dalam usaha membangunkan sistem permintaan makan untuk juvana kerapu harimau, Epinephelus fuscoguttatus, ketajaman dan paksi penglihatan juvana kerapu harimau telah ditentukan untuk mendapatkan pemahaman asas penglihatan. Tiga juvana kerapu harimau dibius dengan MS222 dan diawet dalam larutan Bouin. Retina kiri setiap juvana telah dipotong kepada sembilan bahagian – dorso-nasal (DN), dorsal (D), dorso-temporal (DT), nasal (N), dasar (B), temporal (T), ventro-nasal (VN), ventral (V) dan ventro-temporal (VT). Spesimen-spesimen tersebut ditanam dalam parafin, dipotong secara tangen setebal 6 µm, dan diwarnakan dengan haematoxylin-eosin. Ketumpatan sel-sel kon (0.01 mm2 ) dalam setiap bahagian telah dikira. Ketajaman penglihatan dikira menggunakan ketumpatan sel-sel kon dan diameter kanta. Ketumpatan sel-sel kon tertinggi bagi setiap juvana kerapu harimau adalah 359 (dasar, B), 394 (temporal, T) dan 380 sel/0.01 mm2 (temporal, T) masing-masing. Anggaran ketajaman penglihatan adalah 0.068-0.081 dalam bahagian-bahagian tersebut. Keputusan ini menunjukkan bahawa paksi penglihatan juvana kerapu harimau adalah ke hadapan. Oleh itu, kedudukan suis sasaran sistem permintaan makan ditetapkan pada 2 cm di bawah permukaan air. (Keywords: Brown-marbled grouper; Epinephelus fuscoguttatus; visual acuity; visual axis; demand feeding system)